2016
DOI: 10.1590/1807-3107bor-2016.vol30.0011
|View full text |Cite
|
Sign up to set email alerts
|

Do pediatric medicines induce topographic changes in dental enamel?

Abstract: The purpose of the present study was to evaluate the effect of common pediatric liquid medicines on surface roughness and tooth structure loss and to evaluate the pH values of these medicines at room and cold temperatures in vitro. Eighty-four bovine enamel blocks were divided into seven groups (n = 12): G1-Aliviumand G7-Milli-Q water (negative control). The pH was determined and the samples were immersed in each treatment 3x/day for 5 min. 3D non-contact profilometry was used to determine surface roughness (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…and exposed enamel surface besides the increased surface roughness. The present study provides additional data to our previous study (17), which evaluated the effect of NaF and CPP-ACP/NaF varnishes to inhibit tooth structure loss and alterations in surface roughness after consumption of soft drinks and after pediatric liquid medicine plus soft drink erosion. Based on those previous results (17), Claritin® was chosen to simulate the erosive effects of acid drug and (E) G2 and G5= CPP-ACP/NaF varnish, (C) and (F) G3 and G6= DD water (negative control).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…and exposed enamel surface besides the increased surface roughness. The present study provides additional data to our previous study (17), which evaluated the effect of NaF and CPP-ACP/NaF varnishes to inhibit tooth structure loss and alterations in surface roughness after consumption of soft drinks and after pediatric liquid medicine plus soft drink erosion. Based on those previous results (17), Claritin® was chosen to simulate the erosive effects of acid drug and (E) G2 and G5= CPP-ACP/NaF varnish, (C) and (F) G3 and G6= DD water (negative control).…”
Section: Discussionmentioning
confidence: 79%
“…Other in vitro studies have also demonstrated that Claritin® may reduce enamel hardness (18)(19)(20) and increase surface roughness (17). In the present study, the varnishes were applied once and removed after 6 h of application to simulate the clinical condition, since the emphasis was allowing the chemical effect of the varnish components, rather than the mechanical protection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations